CircWDR78 inhibits the development of colorectal cancer by regulating the miR-653-3p/RGS4 axis - Chu Hao; Yunju Pu; Jiunian Li; Zhi Zhong; Zhaohui Huang; Xue Wang (Journal of Cancer Research and Clinical Oncology)
Abstract Background Colorectal cancer (CRC) stands as one of the most serious threats to human health, with its mortality rate increase during the past years. Low diagnostic accuracy, poor prognosis, and high recurrence rates attributed to the high mortality rate of CRC. Consequently, the urgency to identify potential diagnose and biological targets for intervention in this disease. Among the various molecular factor associated with this disease, circular RNAs (circRNAs) have been a hot topic. These noncoding RNA molecules, characterized by their unique closed loop structure, displayed close associations with the progression of tumors. Methods Actinomycin D experiment and RNA digestion experiment were used to verify the circular structure characteristics of circWDR78. Proliferation and motility ability of circWDR78 was evaluated by in vitro functional experiment. We also used RNA-seq technology to explore the signal pathways and genes it might regulate. Finally, the luciferase assay and qRT-PCR experiment proved that circWDR78 could sponge miR-653-3p, and confirmed that RGS4 is the downstream target of miR-653-3p. Results This study demonstrated that circWDR78 is lower expression in colorectal cancer tissues, revealing its capacity to inhibit proliferation, colony forming ability and cell motility. These findings hint at a potential correlation between its downregulation and the progression of CRC. Mechanistically, we found that circWDR78 could sponge miR-653-3p and identified RGS4 as a novel target of miR-653-3p. Conclusion This discovery highlights the significance of circWDR78 as a potential regulatory axis of miR-653-3p/RGS4 in CRC progression.